Neutron temperature oscilations in neutron multiplication systems and in blankets of thermonuclear reactors - Vodyanitskii, A.A.; Rudakov, V.A. (Вопросы атомной науки и техники, 2011)
Propagation of neutron and temperature oscillations in the neutron multiplication systems is studied. It is shown that the strongly coupled neutron temperature oscillations are resulting from the dependence of the reverse time of neutron capture by the fission nuclei on the "effective" temperature of thermal neutrons.